Ribbon of Peace Banners in Front of Sisk Federal Courthouse - Watkins, Howard::::::::: (1985)
Line of preen cloth red rose, butterflies, flowers and a rainbow on it people holding up Peace banners in front of Sisk Federal Courthouse